Ingestible Wireless Capsule Technology: A Review of Development and Future Indication - M. R. Basar; F. Malek; Khairudi M. Juni; M. Shaharom Idris; M. Iskandar M. Saleh (International Journal of Antennas and Propagation)
Ingestible wireless capsule endoscopy (WCE) is the one and only painless, effective, novel, diagnostic technology for inspecting the entire gastrointestinal (GI) tract for various diseases, such as obscure gastrointestinal bleeding (OGIB), tumors, cancer, Crohn’s disease, and celiac disease. Since the development of this technology, several companies have made remarkable improvements in their clinical products, but there are still some limitations that relate to the use of conventional wired endoscopy. Some of the major limitations that currently impede its wider application include its inability to repeat the view of critical areas, working time constraints, and poor image resolution. Many research groups currently are working on ways to solve these limitations. Presently, developing the ability to control the movement of the capsule, increasing its image transmission speed, and obtaining high-quality images are the main issues in the research area. A complex capsule with some therapeutic tools for the treatment of diseases of the GI tract also is at the beginning of development for the next generation of an active medical robot. In this paper, we report the status of several activities related to WCE, including improvement of capsule technology, research progress, technical challenges, and key indicators concerning the next-generation, active, medical robot.